Analisis Hubungan Struktur Modal dengan Kinerja Keuangan Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2021 - Maretha, Bella; Suharso, Pudjo; Tiara, Tiara (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
This study aims to determine the relationship between capital structure measured by debt to asset ratio and debt to equity ratio with financial performance measured by return on assets in food and beverage subsector manufacturing companies. The data used in this study is secondary data obtained from the company's financial statements for 2018-2021. The subject of this study is a food and beverage subsector manufacturing company listed on the Indonesia Stock Exchange (IDX). This study used the purposive sampling method in determining the research sample so that 33 companies were obtained. Hypothesis testing using Spearman rank correlation test. The results showed that debt to asset ratio and debt to equity ratio have a significant negative relationship with return on assets.